Malignant Breast Lump: To Classify It Based on clinico-demographic Features and To Assess the Correlation Between Tumor Size and Axillary Lymph Node Positivity - Basharat, Maryam; Imran Anwar, Muhammad (Biological and Clinical Sciences Research Journal, 2025)
Breast cancer is a leading cause of mortality in females, accounting for approximately 25% of all breast cancers and contributing to 15% of cancer-related deaths in women. Infiltrating ductal carcinoma is the most common histological type, with axillary lymph node involvement being a critical prognostic factor, particularly in early breast cancer. Objective: To evaluate the relationship between tumor characteristics, size and consistency, and axillary lymph node involvement in breast cancer patients. Methods: This observational cross-sectional study was conducted in the General Surgery and Surgical Oncology Unit of Shaikh Zayed Hospital, Lahore. A total of 165 patients were included using a non-probability consecutive sampling technique. Demographic and clinical data were collected, including tumor size, laterality, site, and consistency, and their relationship with axillary lymph node positivity was analyzed. Results: The mean age of patients was 45.45 ± 6.31 years, and the mean size of malignant breast lumps was 3.57 ± 0.84 cm. Most tumors (88.48%) measured 2-5 cm, while tumors >5 cm and <2 cm accounted for 7.28% and 4.24%, respectively. Left-sided breast lumps were more common (55.15%) than right-sided lumps (44.85%). Tumor size and consistency were significantly associated with axillary lymph node positivity, with p-values <0.05. Conclusion: Axillary lymph node involvement remains an independent risk factor for breast cancer prognosis. Tumor size and consistency are strongly associated with the number of positive lymph nodes, emphasizing their role in the clinical evaluation and management of breast cancer.